Breast necrosis: a rare case of neglected phyllodes tumour - Ho Hui Lian; Theiyallen Ambikapathan; Firdaus Hayati; Nornazirah Azizan; Li Ping Doreen Lee; Siti Zubaidah Sharif (Universiti Putra Malaysia, 2019)
Phyllodes tumour (PT) of the breast is firstly described in literature as early as 1838. This article reports the youngest recorded case of giant complicated PT and the role of toilet mastectomy as a salvage surgery. A 19-year-old lady presented with a gigantic lump of the left breast for 6 months which was rapidly growing (20 x 20 cm) and complicated with a foul-smelling blackish discoloration of the breast skin and tissues. Toilet mastectomy was performed as a result. The specimen weighed 4.0 kg with histopathological report of the tumor being borderline phyllodes. Herein, we describe a case of PT, who presented with breast necrosis and we discuss its medico-social aspect of it.